2015
DOI: 10.1080/10454438.2015.1008286
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed,Enteromorpha intestinalis, as a Diet for Nile TilapiaOreochromis niloticusFry

Abstract: A 42-d feeding trial was carried out to assess the potential use of the seaweed Enteromorpha intestinalis ("gutweed") as a food source for monosex Nile tilapia ( Oreochromis niloticus) fry and to determine a maximum threshold fishmeal substitution rate. Six fish diets randomly assigned to tilapia juvenile and in triplicate were compared: replacing 0%, 10%, 20%, 30%, 40%, and 50% of fishmeal protein with a gutweed protein blend. Highest growth and cost reduction in tilapia fry production was observed in fish fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…had been used to support the growth of aquatic organisms. In a previous study, Ulva lactuca had been developed as a supplement for catfish and tilapia (Abdel-Warith et al 2016;Mahasu et al 2016), while Ulva intestinalis was explored used as an ingredient for tilapia (Siddik et al 2015). Ulva reticulata had also been reported to be a supplement that supported the growth and health of goldfish (Rama et al 2014).…”
Section: Proximate Contentmentioning
confidence: 99%
“…had been used to support the growth of aquatic organisms. In a previous study, Ulva lactuca had been developed as a supplement for catfish and tilapia (Abdel-Warith et al 2016;Mahasu et al 2016), while Ulva intestinalis was explored used as an ingredient for tilapia (Siddik et al 2015). Ulva reticulata had also been reported to be a supplement that supported the growth and health of goldfish (Rama et al 2014).…”
Section: Proximate Contentmentioning
confidence: 99%
“…In this sense, positive effects on weight gain, specific growth rate, and feed use efficiency have been notified for most species when rates are less than 10% of the dry weight of the feed [4,5,39,40]. In contrast, levels of around 10% do not determine changes in the mentioned parameters [6][7][8]41], but higher amounts of 20% or more negatively affect growth parameters [7,9,10,41]. Considering all these preliminary results, in the present work two levels of dietary inclusion, i.e., 5% and 8%, were evaluated.…”
Section: Effect On Nutritional Efficiency and Immune Status Of Juvenile Sea Bass Fed On Diets Including Ulva Previously Treated Or Not Wimentioning
confidence: 99%
“…Hence, positive effects on growth and feed efficiency have been reported at incorporation rates accounting for less than 10% of the dry weight of the feed [4,5]. In contrast, levels exceeding this amount either do not result in significant effects [6][7][8] or produce negative results [9,10]. In this sense, it has been suggested that the presence of protease inhibitors may limit digestive use of this seaweed in several fish species such as the Senegalese sole (Solea senegalensis), the gilthead seabream (Sparus aurata), or the European sea bass (Dicentrarchus labrax,) and hence limiting growth performance and feed use [11].…”
Section: Introductionmentioning
confidence: 99%